The determinants of suppliers' performance in e-procurement: evidence from the Italian government's e-procurement platform - Gian Luigi Albano; Federico Dini; Roberto Zampino; Marta Fana (Fondazione Eni Enrico Mattei (FEEM), 2008)
Participation of small businesses in the market for public contracts is widely recognized as a key policy issue. It is also commonly held that the adoption of e-procurement solutions can be effective in pursuing such an objective. To this end, we analyze the transactions completed in the period 2004-2007 through the Italian Government's e-procurement platform, that is, the marketplace managed by the Italian Public Procurement Agency (Consip S.p.A.). Although descriptive statistics indicate that micro suppliers are the most represented group of firms in the marketplace, our econometric treatment provides some evidence that the former are less successful than all other suppliers in getting public contracts. Degree of loyalty with buyers, location and the use of other MEPA negotiation tools, also emerge as relevant factors of success in the e-procurement market.
Keywords: D44; H57; C16; C25; L25; 330; E-Procurement; Small Suppliers; Request For Quotations; Performance; Public Contracts; Count Data